Water Quality of Groundwater and Diyala River in Jisr Diyala Area within Baghdad City- Iraq - Abbas, Dalal Ahmed; Ali, Kamal K. (Iraqi Journal of Science, 2020)
Groundwater is very important for different uses in the present study area which represents Jisr Diyala, located in southeastern Baghdad and covered with quaternary deposits which include the shallow aquifer in the area. Groundwater and surface water were investigated to determine their suitable uses. The main ion concentrations of the wet period seemed to be lower than those in the dry period. According to TDS values, the water is classified as brackish to salty with a high degree of hardness. Most of water samples were of NaCl type due to pollution with sewage water and rock-water interaction. The results show that the water of the study area is suitable for livestock and irrigation purposes only.